If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 4y = 3y + 14 Reorder the terms: 7x + 4y = 14 + 3y Solving 7x + 4y = 14 + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. 7x + 4y + -4y = 14 + 3y + -4y Combine like terms: 4y + -4y = 0 7x + 0 = 14 + 3y + -4y 7x = 14 + 3y + -4y Combine like terms: 3y + -4y = -1y 7x = 14 + -1y Divide each side by '7'. x = 2 + -0.1428571429y Simplifying x = 2 + -0.1428571429y
| -1a+5=3a+6 | | -8+9k=37 | | -(m+6n-7)= | | (2x-1)(3x+1)=12 | | G(-1)=3(-1+1) | | 29=p | | 4log[6](2x-9)=8 | | x^2=80(x+160) | | -6u+4(u-6)=-12 | | 8(3+t)-3(t+2)= | | 4y+2=10y | | 9[d+2]=2[d+9] | | -2x+4=2(4x-3)-3(-8+4z) | | -x+x^2=31 | | 56.3*3.9= | | 8x^7-20x^4/4x^3 | | 1/4⋅(7.9−2.3) | | -x(x-6)=31 | | 5[m+1]=7[m-11] | | -x(y-6)=31 | | 0.0000000000000000000000000000001+9999999999999999999999999999999= | | F(3)=3*(3*3)-1 | | -31.45=p-12.49 | | F(2)=2*(2*2)-1 | | 16(x+3)=36(x+2) | | 8+9g=10g+10 | | 4073.86=1960+150.99x | | 2x+2-9x=7x+2 | | 12-5=11 | | 14-3(4f-1)= | | -2(5)-5y=20 | | F(1)=1*(1*1)-1 |